Reduced work hours as a means of slowing climate change - Rosnick, David (Washington, DC, 2013)
"As productivity grows in high-income, as well as developing countries, social choices will be made as to how much of the productivity gains will be taken in the form of higher consumption levels versus fewer work hours. In the last few decades, for example, western European countries have significantly reduced work hours (through shorter weekly hours and increased vacation time) while the United States has not. This paper estimates the impact on climate change of reducing work hours over the rest of the century by an annual average of 0.5 percent. It finds that such a change in work hours would eliminate about one-quarter to one-half of the global warming that is not already locked in (i.e. warming that would be caused by 1990 levels of greenhouse gas concentrations already in the atmosphere)."